VO2Max Women's Football Athletes Rokan Hulu Riau - Ridwan Sinurat; Masdi Janiarli; Lolia Manurizal (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
Endurance is one of the elements of physical condition that is indispensable in football. Football is a long game which is about 90 minutes. During this time, players are required to make various movements both with the ball and without the ball to look for opportunities to score goals or defend against opponent attacks. Of course this will make you tired if a player does not have good endurance. Compared to other components such as speed, agility, flexibility and strength, endurance is the most important. Because the ability to perform movements during the game for a long duration is the most important. The purpose of this study was to determine the extent of cardiac endurance of female soccer athletes in Rokan Hulu. This type of research is descriptive qualitative with a cross sectional design. The population is 38 athletes using total sampling technique. The method used in this research is a test survey method. The first stage of this research is to prepare, communicate with athletes for their willingness to be a sample. Second, perform a test using the Multistage Fitness Test instrument. The data collection technique uses a multi-stage test or Multi-stage fitness test (MFT). Analysis of the data used is the percentage. The results showed that athletes had VO2max in the less category (63.16%), while the rest were in the less (21.05%), and moderate (15.79%).